Review of form 483s and warning letters to pharmaceutical manufacturers issued by USFDA. (March 2022) - Saini, Chandan; Miglani, Ashish; Musyuni, Pankaj; Aggarwal, Geeta
Regular inspections are carried out to ensure system conformity by the Food and Drugs Regulatory Authority (FDA) of the United States one of the most stringent regulatory authorities in the world. The inspectors send Form 483 to the management after the inspection, detailing the inappropriate conditions. Because the FDA guidelines are difficult to comply with, a company can contravene the regulations. If any significant infringements can affect the protection, quality, effectiveness, or public health of the drug is identified, the FDA issues advice to the company. Warning Letters (WL) shall be an official notification of non-compliance with federal law within a period to be issued by manufacturer, clinician, distributor, or responsible person in the company. The delivery of a letter has a considerable impact on the company's reputation and position in the market. Inadequate WL reactions could lead to a refusal, import denial, memorandum or even conviction and order. A brief study was conducted in this document of Form 483 and WL for four years (2017–2020) on an understanding the regulatory provisions.